Analysis of Land Certificates issued by the Village Head Against Land Objects Formerly Owned by Customs in Kupang Regency, NTT - Jelian Isra Risandy (Awang Long Law Review, 2021)
documents needed in the registration is a Land Certificate issued by the Village Head. In terms of granting land certificates, sometimes problems arise in the community. Where the provision of the letter is not in accordance with the ownership or physical control of the former customary land controlled by the community. For example, the land area is not suitable and sometimes the letter is not given to people who are entitled to receive a land certificate, as proof of land ownership or control of land that was previously owned by adat. This study uses a type of empirical juridical research with a research location in Kabupaten Kupang, NTT, regarding the analysis of land certificates issued by the village head. The population and sample used purposive sampling technique with the types and sources of data obtained from primary data and secondary data. The technique of collecting Legal Materials uses Field Research. Furthermore, the collected legal materials are then analyzed qualitatively descriptively. Land Certificate issued by the Village Head The Village Head is a valid evidence. The Village Head is given a direct mandate by law to issue a Land Certificate in accordance with the location of the former customary land object owned by the community for various purposes, for example for registration of Property Rights certificates to the National Land Agency (BPN) according to Circular No. 9/SE /VI/2013 concerning Certificate of Ex-Indigenous Land. In addition, for the purpose of buying and selling land based on Government Regulation Number 24 of 1997 concerning Land Registration. As well as proof of the temporary ownership rights for the former customary land object if the community has not had time to register it with the National Land Agency. For the purpose of buying and selling or transferring rights to former customary land, the legal force of a land certificate issued by the Village Head, in the event that this land sale and purchase transaction is based on Government Regulation Number 24 of 1997 concerning Land Registration, will have more legal force if it is known by the The sub-district head as the official making the land deed, with a legal basis based on the Elucidation of Article 7 paragraph (2) and Article 39 paragraph (1) letter (b) number (1) and number (2) Government Regulation Number 24 of 1997 can be categorized as the basis for the rights proposed as completeness of the requirements for the application for land rights.